Exercise Doppler echocardiography of the right heart and pulmonary circulation in patients with cardiovascular risk factors: observations from the RIGHT Heart International NETwork (RIGHT-NET) - De Luca, Mariarosaria; Ferrara, Francesco; Gargani, Luna; Argiento, Paola; Bandera, Francesco; Carbone, Andreina; Castaldo, Rossana; D’Agostino, Anna; D’Alto, Michele; D’Andrea, Antonello; D’Assante, Roberta; Franzese, Monica; et al. (Chest, 2025)
Background - The precise impact of cardiovascular risk factors (CVRFs) on the right ventricle-pulmonary circulation unit remains unclear. - Research Question - Are there any differences regarding resting and exercise right ventricular function in patients with CVRFs but without overt cardiovascular disease when compared with healthy control patients? - Study Design and Methods - We extracted from the RIGHT Heart International NETwork registry the data of 362 patients with at least 1 CVRF but no overt cardiovascular disease and 375 healthy control patients. All patients and control patients had undergone resting and exercise echocardiographic evaluations on a semirecumbent cycle ergometer. Right ventricular-pulmonary arterial coupling was assessed using the ratio of tricuspid annular plane systolic excursion (TAPSE) to pulmonary arterial systolic pressure (sPAP) and pulmonary vascular function through the slope of mean pulmonary arterial pressure (mPAP) to cardiac output (CO) relationship, or dynamic total pulmonary vascular resistance. All-cause mortality and hospitalization events at follow-up were analyzed. - Results - Patients with CVRFs had lower TAPSE/sPAP (P < .001) and a steeper mPAP/CO slope (P < .001) than control patients. A substantial proportion of patients with ≥ 2 CVRFs (38.2%) had mPAP/CO slopes ≥ 3 mm Hg/min/L. Patients with CVRFs also had worse exercise capacity with chronotropic incompetence. The presence of ≥ 2 CVRFs was associated with an additional negative impact on right ventricular systolic function as assessed by TAPSE. The presence of CVRFs affected outcome, with 1 event in healthy control patients compared with 12 events in patients with CVRFs (P < .001). However, no independent effect of TAPSE/sPAP or mPAP/CO was observed, likely due to the limited number of events. - Interpretation - Patients with CVRFs exhibited echocardiographic evidence of right ventricular-pulmonary arterial uncoupling at rest and during exercise, along with elevated dynamic pulmonary vascular resistance, all of which are relevant to exercise capacity. - Clinical Trial Registration - ClinicalTrials.gov; No.: NCT03041337; URL: www.clinicaltrials.gov
Online verfügbar: 19. Juni 2025, Artikelversion: 9. Dezember 2025
Gesehen am 19.02.2026